Updating risk remediation-endpoints for petroleum-contaminated soils? a case study in the Ecuadorian Amazon region - Hidalgo-Lasso, Daniel; García-Villacís, Karina; Ulloa, Jeaneth Urvina; Tapia, Darwin Marín; Ortega, Patricio Gomez; Coulon, Frederic (Elsevier, 2024)
In Ecuador, the regulatory framework for the remediation of petroleum-contaminated soils is based on predefined concentration endpoints for a selected range of petroleum hydrocarbon compounds. However, such approach may lead to over or under-estimation of the environmental risk posed by contaminated soils. In this study, the end-point remediation criteria according to Ecuadorian Environmental legislation were evaluated using different approaches. The first one was based on Total Extractable Petroleum Hydrocarbons (TEPH) and the second one on Total Bioavailable Petroleum Hydrocarbons (TBPH). Both were compared with ecotoxicological determinations using EC50 -Microtox® bioassay at 5 and 15 min of exposure. The correlation (R2) between EC50 values vs TEPH was of 0.2 and 0.25 for 5 and 15 min, respectively. Meanwhile, R2 between EC50 and TBPH was of 0.9 and 0.65 for 5 and 15 min, respectively, demonstrating a stronger correlation. Our results suggest that a contaminated site where the concentration of the TEPH is higher than the relevant regulatory concentrations may be deemed to present an acceptable risk even though their concentrations exceed the target values in soils. The results also challenge the notion that hormesis is associated with TEPH, contrary to some literature. This study is the first in Ecuador to propose incorporating bioavailability into environmental regulations, highlighting the need for further research to establish realistic and achievable remediation goals based on toxicity studies involving various trophic levels.
Keywords: Bioavailability; Total extractable petroleum hydrocarbons; Total bioavailable petroleum hydrocarbons; Hydrocarbon-induced hormesis; Petroleum; Oil-contamination; Risk assessment; Ecuadorian Amazon region